Survei Sarana dan Prasarana Bola Voli di SMA/SMK Se-Kecamatan Suwawa Kabupaten Bone Bolango - Sarjan Mile; Hartono Hadjarati; Arief Ibnu Haryanto (Jendela Olahraga, 2022)
This study aims to survey the volleyball facilities and infrastructure in SMA/SMK in Suwawa District, Bone Bolango Regency. This research is a quantitative descriptive study, the data collection technique is done through a survey, while the data collection tool uses an observation sheet. The samples in this study were SMA Negeri 1 Suwawa and SMK Negeri 1 Suwawa, SMA Terpadu Wira Bhakti. As a result, SMA Negeri 1 Suwawa has a moderate amount of facilities and infrastructure, moderate condition of facilities and infrastructure, and good ownership of facilities and infrastructure. SMK Negeri 1 Suwawa has a number of good facilities and infrastructure, good condition of facilities and infrastructure, and ownership of good facilities and infrastructure. SMA Terpadu Wira Bhakti has fewer facilities and infrastructure, poor condition of facilities and infrastructure, and very little ownership of facilities and infrastructure. The conclusions of this study suggest that SMA/SMK in Suwawa Sub-district, Bone Bolango Regency in general already have adequate volleyball facilities and infrastructure, but still need some improvements.